Development of a µ-TPC detector as a standard instrument for low-energy neutron field characterisation. Issue 1 (3rd March 2014) - Maire, D.; Billard, J.; Bosson, G.; Bourrion, O.; Guillaudin, O.; Lamblin, J.; Lebreton, L.; Mayet, F.; Médard, J.; Muraz, J. F.; Richer, J. P.; Riffard, Q.; et al.
Abstract : In order to measure the energy and fluence of neutron fields, in the energy range of 8 to 1 MeV, a new primary standard is being developed at the Institute for Radioprotection and Nuclear Safety (IRSN). This project, Micro Time Projection Chamber (µ-TPC), carried out in collaboration with the Laboratoire de Physqique Subatomique et de Cosmologie (LPSC), is based on the nucleus recoil detector principle. The measurement strategy requires track reconstruction of recoiling nuclei down to a few kiloelectronvolts, which can be achieved using a micro-pattern gaseous detector. A gas mixture, mainly isobutane, is used as an n-p converter to detect neutrons within the detection volume. Then electrons, coming from the ionisation of the gas by the proton recoil, are collected by the pixelised anode (2D projection). A self-triggered electronics system is able to perform the anode readout at a 50-MHz frequency in order to give the third dimension of the track. Then, the scattering angle is deduced from this track using algorithms. The charge collection leads to the proton energy, taking into account the ionisation quenching factor. This article emphasises the neutron energy measurements of a monoenergetic neutron field produced at 127 keV. The fluence measurement is not shown in this article. The measurements are compared with Monte Carlo simulations using realistic neutron fields and simulations of the detector response. The discrepancy between experiments and simulations is 5 keV mainly due to the calibration uncertainties of 10 %.